Comportamento de cultivares de feijão-caupi ao parasitismo de Meloidogyne spp. e avaliação do efeito da salinidade na eclosão, motilidade, sobrevivência e infectividade de M. enterolobii - Magalhães, Pedro Rodrigues (2018)
The root-knot nematodes, Meloidogyne spp., are the most important phytonematoids in the world, as they infect cultivated plants and adapt more to different types of environments, what contributes to their greater dispersion. In Brazil, there are more than 20 species, notably M. incognita, M. javanica, M. arenaria, M. hapla and M. enterolobii. In the state of Ceará, in addition to the five species, M. konaensis has recently been reported. Such phytoparasites affect crops, including cowpea (Vigna unguiculata (L.) Walp), a well adapted species of the Northeast semiarid. In addition, another condition that affects crop productivity is the salinity, one of the major abiotic limiting factors. On the other hand, “Pitiúba” cowpea has a good ability to adapt to the saline stress. However, instructions on the behavior of gall nematodes in environments with high levels of salinity are still scarce. Based on the above, the objective of this work is: 1) to verify the hospedability of the cowpea cultivars Pitiúba, Sempre Verde, João Paulo II and Setentão to M. incognita, M. arenaria, M. enterolobii and M. konaensis; 2) to evaluate the hatchability of J2 fase of M. enterolobii in saline solution at NaCl levels of 100 mM. 3) to evaluate motility and survival of J2 fase of M. enterolobii in saline at NaCl levels of 0, 25, 50, 75, 100, 125, 150, 175, 200, 300 and 400 mM; 4) to investigate the infectivity and the development of M. enterolobii in “Pitiúba” cowpea under irrigation with saline at the NaCl level of 100mM. It was observed that the Pitiúba cultivar was the only one susceptible to M. enterolobii, whereas ‘João Paulo II’ presented resistance only to this species. João Paulo II and Setentão cultivars were susceptible to M. konaensis. J2 hatching, motility and juvenile survival of M. enterolobii were found to be unaffected by salinity levels tested in vitro. In ‘Pitiúba’ plants irrigated with saline solution at NaCl levels of 100 mM, the infectivity of M. enterolobii was not affected; however, the development of its phases in the infected roots was compromised.